Uji Antagonis Bacillus subtilis ATTC 6633 dan Trichoderma harzianum terhadap Pertumbuhan Magnaphorte oryzae pada Benih Padi Anak Daro dengan Variasi Lama Perendaman - Alamsjah, Feskaharny; Noli, Zozy Aneloi; Rahmayati, Riesca Salsabilah; Suwirmen, Suwirmen; Agustien, Anthoni; Ilham, Kurniadi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Magnaphorte oryzae is a pathogenic fungus that causes blast disease in rice plants. This disease can cause a decrease in rice production. Therefore, it is necessary to control the disease, one of which is by administering microbes that are antagonistic to Magnaphorte oryzae. This research aims to determine the percentage of inhibitory power of Bacillus subtilis ATTC 6633 and Trichoderma harzianum on the growth of Magnaphorte oryzae with varying soaking times of 24, 48 and 72 hours on the Anak Daro rice variety. This research carried out viability tests for Bacillus subtilis ATTC 6633 and Trichoderma harzianum, as well as antagonist tests using the dual culture method. The results showed that the growth inhibition of Magnaphorte oryzae by Bacillus subtilis ATTC 6633 for a soaking period of 24 hours was 28.48% in the weak category, 48 hours was 32.27% and 72 hours was 31.01% in the medium category. Inhibition of Magnaphorte oryzae by Trichoderma harzianum for a soaking period of 24 hours was 50.63%, 48 hours was 57.59%, and 72 hours was 56.32% in the high category.